Efficacy and Safety of Different Aerobic Exercise Intensities in Patients With Heart Failure With Reduced Ejection Fraction: Design of a Multicenter Randomized Controlled Trial (HF-EI Trial) - Shen, Ting; Liu, Xiaoling; Zhuang, Bo; Luo, Qian; Jin, Yishan; Li, Guanghe; Jiang, Yumei; Li, Dejie; Chen, Xianchuan; Tang, Nuo; Xu, Zhimin; Wang, Lemin; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Heart failure (HF) is one of the major causes of mortality worldwide, representing the terminal stage of several cardiovascular diseases. Exercise-based rehabilitation is a beneficial therapy for patients with chronic heart failure (CHF). However, there is a lack of specific guidance on clinical decision-making regarding optimal exercise intensity. It is necessary to optimize the clinical recommendations for HF exercises. We will evaluate the efficacy and safety of different aerobic exercise intensities in patients with heart failure with reduced ejection fraction (HFrEF): the HF-EI trial. This trial aims to assess the appropriate exercise intensity for patients with HFrEF. Methods: After a baseline assessment to determine the safety of exercise, 180 patients will be randomly assigned to supervised high-intensity exercise training (ET) group, supervised moderate intensity training (MIT) group, and control group at a ratio of 1:1:1. Patients randomly receiving high intensity training (HIT) undergo supervised ET (3 times/week, 30 min) for aerobic endurance at 70% peak oxygen consumption (peak VO2) intensity for 12 weeks. The MIT patients will perform supervised aerobic ET (3 times/week, 35–42 min) at the anaerobic threshold (AT) intensity for 12 weeks. The control group will continue to maintain their daily activities and will not receive ET. During the baseline and follow-up period, physical examination, laboratory tests, cardiology diagnostic tests, cardiopulmonary exercise tests (CPET), 6-min walk distance (6MWD), scale scores, exercise steps, medications, and clinical events will be monitored. Throughout the research, sport bracelets and patient diaries will be used to monitor and record overall physical activity, training courses, and compliance. Discussion: The HF-EI trial will evaluate the effects of different aerobic exercise intensities on peak VO2, quality of life (QoL), and clinical events among patients with HFrEF. The findings of this trial will provide a basis for formulating exercise prescriptions for patients with HFrEF. Clinical Trial Registration:http://www.chictr.org.cn/, identifier: ChiCTR2000036381.